Peran Kepemimpinan, Kelembagaan, dan Modal Sosial Dalam Pembangunan Wilayah: Studi Kasus Pengelolaan Sampah Zero Landfill Kabupaten Banyumas - Januarta Dwi Kusmayanti; Deshinta Sekar Ayuningtyas (Jurnal Kebijakan Pemerintahan, 2025)
Abstract Sustainable waste management remains a critical challenge amid increasing demands for environmentally oriented regional development. This study examines the role of leaderships, institutions, and social capital in supporting zero-landfill waste management in the Banyumas Regency, Indonesia. Using a qualitative desk research approach based on policy documents, secondary statistical data, and relevant literature, this study adopts an endogenous perspective to analyze how waste management functions as a catalyst for local economic and social development. The findings indicate that visionary leadership plays a strategic role in integrating waste management into regional development planning and fostering cross-sector collaboration. Institutional strengthening enables effective coordination among government agencies, community-based organizations, and private sector actors, while social capital enhances community participation and supports the emergence of waste-based local entrepreneurship. Although the contribution of the waste sector to regional GDP remains limited, the analysis demonstrates substantial economic and social benefits at the community level, including job creation, income generation, and operational efficiency. This study highlights that the integration of leadership, institutions, and social capital constitutes a critical prerequisite for building a sustainable and adaptive waste management system within an endogenous regional development framework. Keywords: endogenous development, institutions, leadership, social capital, waste management.